2018
DOI: 10.2166/wst.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

A novel image processing-based system for turbidity measurement in domestic and industrial wastewater

Abstract: Wastewater treatment facilities are continually challenged to meet both environmental regulations and reduce running costs (particularly energy and staffing costs). Improving the efficiency of operational monitoring at wastewater treatment plants (WWTPs) requires the development and implementation of appropriate performance metrics; particularly those that are easily measured, strongly correlate to WWTP performance, and can be easily automated, with a minimal amount of maintenance or intervention by human oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 49 publications
0
12
0
2
Order By: Relevance
“…In future, it is envisaged that the turbidity of the supernatant could also be examined, as it is indicative of effluent turbidity. From the work conducted previously (Hongve and Åkesson, 1998;Mullins et al, 2018), it is known that IR light is required for this analysis, as the dissolved organic matter present absorbs broadband white light in different ways. Also, the camera used for this analysis was unsuitable for viewing IR light, as like most consumer cameras, it contains an IR-UV cut filter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future, it is envisaged that the turbidity of the supernatant could also be examined, as it is indicative of effluent turbidity. From the work conducted previously (Hongve and Åkesson, 1998;Mullins et al, 2018), it is known that IR light is required for this analysis, as the dissolved organic matter present absorbs broadband white light in different ways. Also, the camera used for this analysis was unsuitable for viewing IR light, as like most consumer cameras, it contains an IR-UV cut filter.…”
Section: Discussionmentioning
confidence: 99%
“…There has been ongoing research in wastewater assessment and monitoring over the last 20-30 years highlighting the need for the development of low-cost and robust sensors that are capable of providing real-time feedback, therefore enabling operators to make informed decisions (Council of the European Communities, 1991; Gitelson et al, 2008;Mullins et al, 2018). Furthermore, optimising the performance of WWTPs is a key area of focus for the sector in order to meet discharge limits, set by EU legislation (European Commission, 1998;Kim and Hao, 2001;Fitzsimons et al, 2016), as well as reducing operational costs (Fernández et al, 2011;O'Reilly et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A novel and automatic turbidity estimation system for fluids was proposed [24]. Effluent samples are imaged such that the light absorption characteristic is highlighted as a function of fluid depth and computer vision processing techniques are used to quantify this characteristic.…”
Section: B Comparing With the Latest Image Methods For Turbidity Meamentioning
confidence: 99%
“…Process performance and floc structure were assessed using computer imaging by Oliveira, Alliet, Coufort-Saudejaud, and Frances (2018) under various conditions. Mullins et al (2018) demonstrated a system for measuring turbidity using computer visioning. Savings in the order of 80% were reported by Lockey and Bhartia (2018) following the implementation of a food processing automated dissolved air flotation (DAF) control platform including online sensors, control algorithms based on artificial intelligence (AI) and remote monitoring was presented.…”
Section: Automation and Controlmentioning
confidence: 99%